Karakterisasi reaktor plasma berarus positif dengan konfigurasi elektroda multi garis-bidang - Sholehah Aisyah; Muhlisin Zaenul; Arianto Fajar (Youngster Physics Journal, 2017)
Plasma technology is the most widely researched technology. Research on various types of plasma reactors began much done in order to obtain plasma which has high homogeneity. This study aims to obtain plasma discharge characteristic I-V relations in the plasma reactor wire-plate electrode configuration. This study uses nine electrodes wire with a length of 12 cm and a diameter of 0.38 mm as the positive electrode and PCB as a negative electrode plates. Characterization of plasma corona wire-plate is done by adjusting the distance between the electrodes of 1.8 cm, 2.1 cm, 2.4 cm, 2.7 cm, 3.0 cm, 3.3 cm, 3.6 cm, 3.9 cm, 4.2 cm, and 4.5 cm. The results showed that the current increases with the applied voltage and inversely proportional to the distance between the electrodes. In the future this method it is possible to be applied on an industrial scale.Keywords: Plasma corona, plasma corona wire-plate